Differences in Development and Diet of Stunting and Non-Stunting Children in the Rowosari Health Center Work Area, Semarang, Indonesia - Avionita Latuihamallo; Ani Margawati; Maria Mexitalia; Annastasia Ediati; Ahmad Syauqy (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2022)
Background: Stunting in children aged 36-59 months is caused by the intake of energy and protein below the average RDA recommendation. This low consumption has an impact on different growth and development disorders.Objectives: This study aimed to determine the differences in the development and diet of stunted and non-stunted children aged 36-59 months.Materials and Methods: This was an observational study with a cross-sectional approach, which was carried out at the work area of the Rowosari Health Center. The sample population consisted of 67 children aged 36-59 months, which were selected using the simple random sampling technique. The characteristics of the subjects and mothers were then collected using a questionnaire. Meanwhile, data on the diet and child development were obtained with the 24-hour recall method and Developmental Pre-Screening Questionnaire (KPSP), respectively.Results: The results showed that there were differences in the development as well as energy and protein adequacy level of stunted and non-stunted children with a p-value <0.05.Conclusion: There were several deviant developments in non-stunted toddlers due to the lack of nutritional intake, stimulation, interaction with the environment as well as the low knowledge of mothers about child care patterns.